Socially equitable climate risk management of urban heat - Michael Friesenecker; Antonia Schneider; Marianne Bügelmayer-Blaschek; Michael Getzner; Claudia Hahn; Martin Schneider; Sebastian Seebauer; Wojciech Zawadzki; Maja Zuvela-Aloise; Thomas Thaler (npj Urban Sustainability)
Abstract As the management of extreme weather events becomes increasingly important, climate adaptation strategies are paramount. However, current climate adaptation strategies often overlook aspects of social inequality or even risk exacerbating these. An example is the implementation of Nature-based Solutions (NbS). These approaches can result in green gentrification; the displacement and exclusion of marginalized groups due to increased attractiveness and value of nearby property. The consideration of social impacts into climate adaptation policies represents a significant challenge because climate policies are usually determined independently from social policies (policy siloing). Here we demonstrate a decision-making process that ensures socially equitable climate adaptation in an urban area. The proposed decision-making framework consists of three sequential stages: (1) climate risk assessment, (2) adaptation analysis, and (3) impact analysis. This decision-making method is applicable to cities worldwide. The City of Vienna, Austria and NbS are used to illustrate how climate adaptation policy can be integrated with social policy to achieve socially equitable urban heat risk management. We showcase that breaking current policy silos is necessary to achieve a socially equitable climate change adaptation strategy.